GRK Inhibition Potentiates Glucagon-Like Peptide-1 Action - Lee, Seunghun P.; Qi, Jenson; Xu, Guozhang; Rankin, Matthew M.; Littrell, James; Xu, June Zhi; Bakaj, Ivona; Pocai, Alessandro (Frontiers in Endocrinology, 2021)
The glucagon-like peptide-1 receptor (GLP-1R) is a G-protein-coupled receptor (GPCR) whose activation results in suppression of food intake and improvement of glucose metabolism. Several receptor interacting proteins regulate the signaling of GLP-1R such as G protein-coupled receptor kinases and β-arrestins. Here we evaluated the physiological and pharmacological impact of GRK inhibition on GLP-1R activity leveraging small molecule inhibitors of GRK2 and GRK3 (GRK). We demonstrated that inhibition of GRK: i) inhibited GLP-1-mediated β-arrestin recruitment, ii) enhanced GLP-1-induced insulin secretion in isolated islets and iii) potentiated dipeptidyl peptidase 4-mediated suppression of glucose excursion in mice. These findings highlight the importance of GRK to modulate GLP-1R function in vitro and in vivo. GRK inhibition is a potential therapeutic approach to enhance endogenous and pharmacologically stimulated GLP-1R signaling.